IMPACT OF THE COMMON AGRICULTURAL POLICY ON NATIONAL ECONOMY – ILFOV COUNTY STUDY CASE - Octavian Constantin BURGHELEA; Oana Camelia IACOB; Ana-Maria VOLINTIRU; Anca CRISTEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This article aims to highlight the fact that Romania's accession to the European Union had a major impact on all sectors of the national economy, particularly on agriculture, due to the application of CAP-specific funding tools and mechanisms for addressing farms producing for the market. Since EU mechanisms for supporting agriculture are diverse and will evolve further in this direction, Romania must simplify and redirect their support so that the current types and forms, highly diversified and with difficult to estimate favorable effects, will be able to insure convergence with CAP.